Estudio fitoquímico las especies cymbopogon citratus, melissa officinals y aloysa citrodora. - Espinoza Blacio, Brenda Estefania (2015)
In the present investigation hexane extracts of Cymbopogon citratus and methanol, Melissa officinalis and Aloysa citrodora, the same as were characterized by thin layer chromatography (TLC) they were obtained. Acetone (4:1) and the methanol extract, hexane: acetone (7:3) extracts for both the chromatographic profile of each species using as stationary phase silica gel GF254 as mobile phase to the hexane extract, hexane was obtained. The revealed by UV light suggested the presence of structures with conjugated chromophores, metabolites further separation using H2SO4, heat and vanillin visualized.